Human Rickettsia felis infections in Mainland China - Teng, Zhongqiu; Zhao, Na; Ren, Ruotong; Zhang, Xue; Du, Zhenshan; Wang, Pengfei; Qin, Tian (Frontiers in Cellular and Infection Microbiology, 2022)
A retrospective survey of patients with fever of unknown origin (FUO) in mainland China identified four patients with flea-borne spotted fever caused by Rickettsia felis using molecular methods. Plasma or bronchoalveolar lavage fluid collected from 187 patients with FUO between 2021 and 2022 were screened and analyzed. Cases positive for R. felis were sporadic in several provinces of mainland China. The clinical signs and symptoms of the patients were similar to those of other rickettsioses, including fever, rash, and liver and kidney dysfunction. All four patients in the present study developed pneumonia or lung lesions after R. felis infection. R. felis is a neglected flea-borne pathogen. The prevalence (2.14%, 4/187) of R. felis among patients with FUO is considered high and highlights the risk posed by the pathogen to public health in China.